HYDRONYMS OF ADYGEA AS A SOURCE OF ETHNOCULTURAL INFORMATION (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-75-85The article is devoted to the study of a group of regional hydronyms that have lost their connection with the appellative. It is established that the study of the etymology, semantics of a hydronym, the definition of its original appearance is impossible without the involvement of ethnocultural material, which confirms the need to use an integrated approach to the study of toponyms, since such an approach makes it possible to correctly describe units and allows for the «reconstruction» of the regional toponymic space, toponymic field.Purpose: The description of the toponymic space of the region (the Republic of Adygea) and hydronyms in particular involves a detailed analysis of all units, allowing to reflect the entire toponymic picture. In the toponymy of the region, there are names that have lost their connection with appellatives. The establishment of etymology, semantics and the initial appearance of such units is impossible without the involvement of ethno-cultural material. Such an approach provides an opportunity that makes it possible to carry out a correct description of units and allows for the «reconstruction» of the regional toponymic space.Methods: The basis for the correct description of the etymology and semantics of names of specific geographical objects is the conservatism of toponymic models characteristic of the language. The research was conducted using phonetic, word-formation, etymological, semantic analysis. The basis for solving ethnolinguistic problems was the combination of onomasiological and semasiological aspects of research.Results: To establish the etymology of a toponym, it is necessary to take into account the principles of nomination characteristic of the self-consciousness and worldview of the people inhabiting a certain territory, reflected in culture and language, as well as the place of a specific name in the systemic organization of the regional toponymic field. Ethnocultural information captured in toponymy is what helps a linguist researcher to determine the principles of nomination characteristic of a particular language reflecting the worldview of the people.Discussion: The description of the toponymic space of the region (not only the Republic of Adygea), taking into account the system relations and the field approach, the identification of the main nomination techniques, clarification of the etymology, semantics of individual geographical objects traditionally associated with the regional landscape and being components of the regional onomastic field, seems very relevant and promising. The detailed analysis of hydronyms allows reconstructing the entire toponymic space of the region, makes it possible to consider the entire system as a whole. Key words: toponymy, hydronym, Adygea, appellative, toponymic space Acknowledgments. The research was carried out with the financial support of the Adygea State University Agreement 21/21 dated 08.12.2021 within the framework of the scientific project "Reactualization of the toponymic space of the Republic of Adygea: linguistic and cultural content of the tourist cluster".